Penyuluhan dan Pemeriksaan Feses Pada Masyarakat Desa Bone Kecamatan Nekamese Sebagai Upaya Pencegahan Penyakit Tropis - Aldiana Astuti; Wilhelmus Olin; Marni Tangkelangi; Adrianus Ola Wuan (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Hookworm infection remains a significant health concern, particularly in rural areas like Bone Village, Nekamese District. This community service project aimed to conduct health education and stool examinations to prevent and control tropical diseases. Stool examinations were performed on 60 samples from the Bone Village community, revealing that 2 samples tested positive for hookworm eggs, indicating the presence of hookworm infection, although the prevalence was relatively low. Following this, an interactive health education session was conducted on March 24, 2024, at the village church, involving the local community. The educational materials covered the prevention and treatment of hookworm infection, the importance of personal and environmental hygiene, and how to detect early symptoms of tropical diseases. This activity successfully raised community awareness about the importance of preventing tropical diseases and was published in the online media Kupang, reaching a broader audience. The results of the community service project demonstrated that a participatory and educational approach is effective in reducing the risk of hookworm infection and improving overall community health